Anomalies In Asian Stock Market - Kamaludini (Media Riset Akuntansi, Auditing & Informasi, 2008)
Anomaly phenomena in many stock markets show various results achieved by each researcher. The various results very much depend on time and method used. Most of Asian Stock Market is emerging market. The objective in this research are to know market anomalies, especially those of weekend effect, turn of the month effect, and turn of the yeareffect, in Asian stock markets region. The analysis methods to test for market anomalies are GARCH and AAIOVA. The result in this research is: anomalies that happen on weekend effect and turn of the month effect. Anomalies on the turn of the year effect in this research show no significant result. Anomaly will occur in several condition, in weekend and early of the week, turn of and first the month. Anomaly will happen also in several event, such as; independent and religious day.Key words : Emerging market, GARCH, ANOVA, market anomaly, weekend effect, turn of the month effect, and turn of the year effect.